Constructing a conceptual framework of the smart apparel design using KJ methods for the disabled elderly - Jamian, Juliza; Shaari, Nazlina (Faculty of Arts, Computers and Creative Industries, Universiti Pendidikan Sultan Idris, 2018)
This study is to extract the keywords from the literature review as the guideline factor to construct the best conceptual framework of the smart apparel design for disabled elderly in folks' home. Based on the problem occurred in Old Folks Home in Kajang, Selangor, fifteen disabled elderly at the aged of 50 to 70 years old with half body paralysed were participating in this study. Recently, the patients or health worker is having difficulties in changing disabled, elderly garments. They are also facing various problem on the accessibility for medical examination daily in the Folks Home Centre. The KJ method technique and literature reviews is used to develop the conceptual framework in order to identify the gap and needs of the user in their daily garment. As the result, this conceptual paper provides the classifying knowledge transfer in constructing smart apparel design for disabled elderly in an old folks home as the guideline that can improve the conceptual framework.